Effectiveness of a miswak extract‐containing toothpaste on gingival inflammation: a randomized clinical trial. Issue 3 (22nd December 2015) - Azaripour, A; Mahmoodi, B; Habibi, E; Willershausen, I; Schmidtmann, I; Willershausen, B
Abstract: Objectives: In this study, the efficacy of a miswak extract‐containing toothpaste ( Salvadora persica ) on gingival inflammation was compared with that of a herbal and a conventional toothpaste. Methods: Non‐smoking outpatients with sulcus bleeding index (SBI) ≥25% and with periodontal pocket depths ≤3 mm were randomly selected and divided into three groups: M‐group, miswak extract‐containing toothpaste; P‐group, herbal toothpaste; and C‐group, conventional toothpaste. After instructing the patients to brush their teeth twice a day for 3 weeks with the assigned toothpaste using a flat‐trimmed manual toothbrush, a thorough oral examination was performed by a calibrated examiner (EH). The primary outcome was the SBI after 21 days. Furthermore, the amount of plaque was measured by approximal plaque index (API). Results: Sixty‐six patients with a mean age of 57.8 ± 10.2 years were recruited and enrolled. After 3 weeks of brushing, all three patient groups showed a significant reduction in SBI. The P‐group (SBI reduction: 17.1% ± 9.1) and the M‐group (14.5% ± 8.1) showed the strongest effect followed by the C‐group (9.4% ± 7.8). All three groups showed a significant reduction in API without significant differences between the groups. Conclusions: The use of each of the three tested toothpastes caused a significant reduction in gingival inflammation and amount of plaque. The miswak extract‐containing toothpaste showed a similar effect as the herbal toothpaste and can be safely used for domestic oral hygiene in patients with gingivitis.